2012
DOI: 10.1186/1472-6947-12-121
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone and medical related App use among medical students and junior doctors in the United Kingdom (UK): a regional survey

Abstract: BackgroundSmartphone usage has spread to many settings including that of healthcare with numerous potential and realised benefits. The ability to download custom-built software applications (apps) has created a new wealth of clinical resources available to healthcare staff, providing evidence-based decisional tools to reduce medical errors.Previous literature has examined how smartphones can be utilised by both medical student and doctor populations, to enhance educational and workplace activities, with the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
479
9
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(541 citation statements)
references
References 20 publications
41
479
9
12
Order By: Relevance
“…A study showed that in 24 hours, apps for disease diagnosis/management and drug reference app were used for between 1-30 minutes by students and 1-20 minutes by doctors who favored using clinical score/calculator apps. 26 Lanaj et al reported that smartphone use for work at night increased depletion the next morning via its effects on sleep, morning depletion in turn diminished daily work engagement which was incremental to the effects of other electronic devices like computer, TV tablet etc. 27 Apart from its effect on sleep, smartphone addiction has effect on physical and psychological health; other than smartphone addiction, sleep quality itself has many determinants among students in general and among medical students in particular.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that in 24 hours, apps for disease diagnosis/management and drug reference app were used for between 1-30 minutes by students and 1-20 minutes by doctors who favored using clinical score/calculator apps. 26 Lanaj et al reported that smartphone use for work at night increased depletion the next morning via its effects on sleep, morning depletion in turn diminished daily work engagement which was incremental to the effects of other electronic devices like computer, TV tablet etc. 27 Apart from its effect on sleep, smartphone addiction has effect on physical and psychological health; other than smartphone addiction, sleep quality itself has many determinants among students in general and among medical students in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the outcomes of patient-centered care have reported better recovery from their discomfort and concern, better emotional health, and fewer diagnostic tests and referrals (Cliff, 2012;Gabriel & Normand, 2012;Oates, Weston, & Jordan, 2000). Additional studies have also shown that the use of mHealth applications for patient-centered care reduce the cost of care significantly (Boulos, Wheeler, Tavares, & Jones, 2011;Payne, Wharrad, & Watts, 2012). Medical applications make smartphones useful tools in the practice of evidence-based medicine at the point of care (Mosa, Yoo, & Sheets, 2012).…”
Section: Mobile Health (Mhealth) For Equitable Healthcarementioning
confidence: 99%
“…Physicians Information Technology for Developmentand medical students are also increasing their usage to support their education and clinical practice (Payne et al, 2012;Ventola, 2014). The increased popularity of smartphones has led more patients to proactively manage their care while on the go using specific mobile applications containing functionalities such as GPS tracker for Alzheimer's patients, not available on desktop computers (Qureshi, Noteboom, & Schumaker, 2015).…”
Section: Mobile Health (Mhealth) For Equitable Healthcarementioning
confidence: 99%
“…Although such studies have been reported we did not find any scholarly articles In PUBMED or Google scholar with searches using key words Apps and ADHD. On the other hand, a recent study highlighted the popularity of smartphones and apps for their education and clinical work 13 . However, limitations in relation to iPhone apps and the paucity of research in relation to their development from a limited survey were noted 14 .…”
Section: Introductionmentioning
confidence: 99%